Apoptose no tecido lamelar de equinos submetidos a dois modelos de laminite séptica e sua correlação com a presença de leucócitos - Antônio Catunda Pinho Neto (2019)
The process of programmed cell death (apoptosis) is a mechanism where cells actively participate, producing caspases in response to a range of stimuli, counterbalancing mitosis or seeking homeostasis. However, when it occurs exacerbated, in a lamellar interface, in patients with acute or chronic laminitis, with a failure in support structures and adherence of the phalanx distal to the hoof. The objective of this work was to verify the occurrence of apoptosis in black walnut extract (BWE) and starch overload (CHO) models using the TUNEL technique and to correlate with findings of neutrophils and monocytes in the different stages of development of laminitis in both groups. For this purpose, 20 animals were used in the model of black walnut extract equally allocated in the groups Controls (CON = 5), Earlier Time Point (ETP = 5), Later Time Point (DTP = 5) and Obel 1 (OG 1 = 5). As for the starch loading model, 25 animals were allocated to the Control (CON = 8), Later Time Point (DTP = 6), Obel 1 (OG 1 = 6) and Obel 3 (OG 3 = 5). The samples were treated and processed for the TUNEL technique of apoptosis and immunohistochemistry for neutrophils and monocytes. The models of laminitis by black walnut extract and starch overload produce different effects on the occurrence of apoptosis in lamellar tissue keratinocytes, with reduction during development and onset of claudication in the BWE model. This, in turn, presented a negative correlation between apoptosis and leukocyte infiltration, demonstrating that concomitant increase of leukocyte infiltrate occurs with reduction in the occurrence of apoptosis in the lamellar tissue, suggesting a potential cytoprotective effect of black walnut extract.